Sosialisasi Pemanfaatan Teknologi Digital Dalam Mengoptimalkan Penjualan Pada UMKM - Arianto, Arianto; Choirunnisa, Choirunnisa; Setiawan, Hendy; Rahmawati, Anik (Universitas Negeri Gorontalo, 2025)
The rapid development of digital technology has significantly impacted various sectors, including micro, small, and medium enterprises (MSMEs). However, the lack of knowledge and skills in accessing and utilizing digital technology has made MSME entrepreneurs in Kedungsegog Village struggle to compete in an increasingly competitive market. As a result, they often miss opportunities to optimize sales and grow their businesses. Therefore, this community service activity aims to enhance MSME entrepreneurs' understanding of digital technology utilization in marketing strategies and business operations. The activity was conducted through direct (offline) socialization, including material presentations and interactive discussions. The results show an increased understanding among MSME entrepreneurs regarding the importance of digital technology in supporting their businesses, particularly in marketing, operational efficiency, and information access. Additionally, MSME entrepreneurs have shown motivation to optimize customer service and expand their market reach to the regional level. To ensure the sustainability of this initiative's impact, follow-up mentoring programs are needed so that the adoption of digital technology can be consistently and optimally implemented in their business management.